OPTIMAL PAYMENT CONTRACTS IN TRADE RELATIONSHIPS - Christian Fischer-Thöne (International Economic Review, 2023)
In buyer–seller relationships, offering trade credit to buyers fosters long-term collaboration but seller provision varies systematically as relationships evolve. We study the optimal provision dynamics of trade credit when the seller's information about the buyer is incomplete. We show how the interaction of self-enforcing relational contracts and formal contracts determines optimal payment contract choice. We find that payment contracts can be interpreted as screening technologies and imply distinct learning opportunities about the buyer's type. In line with empirical evidence, the model predicts that all transitions between payment terms lead to seller trade credit provision in the long run.
Keywords: 330